Victorian literature - Amigoni, David (Edinburgh : Edinburgh University Press, 2011)
How were the genres of literature changed by new methods of serialization and publishing? How did a widespread culture of performance emerge in the period to shape as well as to be shaped by the novel and poetry? David Amigoni draws on the most recent critical approaches to the novel, Victorian melodrama and poetry to answer these and other questions. The work of Charles Dickens, George Eliot, Oscar Wilde, Alfred Tennyson, Robert Browning, Christina Rossetti, Thomas Hardy, Thomas Carlyle and Mathew Arnold are explored in relation to ideas about fiction, journalism, drama, poetry, the New Woman, gothic, horror and the Victorian sage. Key Features Detailed readings of key texts provide models of how to read critically Demonstrates the interaction between genres to help think through modes of artistic experimentation and innovation in the period Examines Neo-Victorian fiction, a popular genre today Student resources include electronic and reference sources, further reading and an extensive glossary of key critical terms and historical issues
Cover; Copyright; Contents; Series Preface; Acknowledgements; Chronology; Introduction to Victorian Literature: Perspectives, Relationships, Contexts; Chapter 1 Novel Sensations in Early and Mid-Victorian Fiction: From 'Boz' to Middlemarch; Chapter 2 Theatrical Exchanges: Gendered Subjectivity and Identity Trials in the Dramatic Imagination; Chapter 3 Poetry: Dramatic Monologues and Critical Dialogues; Chapter 4 Victorians in Critical Time: Fin de Siècle and Sage-culture; Conclusion: Neo-Victorianism, Postmodernism and Underground Cultures; Student Resources; Index.
Includes bibliographical references (pages 198-205) and index.
Print version record.
English.
JSTOR
Keywords: English literature -- 19th century -- History and criticism; Great Britain -- History -- Victoria, 1837-1901.; Littérature anglaise -- 19e siècle -- Histoire et critique; Grande-Bretagne -- Histoire -- 1837-1901 (Victoria); LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; LITERARY CRITICISM -- Mystery & Detective; English literature; Great Britain; Literatur; Bellettrie; Verenigd Koninkrijk van Groot-Brittannië en Noord-Ierland.; Englisch; 1800-1901; Criticism, interpretation, etc; History